The Potential Application of Green-Synthesized Metal Nanoparticles in Dentistry: A Comprehensive Review. (3rd March 2022) - Yazdanian, Mohsen; Rostamzadeh, Pouya; Rahbar, Mahdi; Alam, Mostafa; Abbasi, Kamyar; Tahmasebi, Elahe; Tebyaniyan, Hamid; Ranjbar, Reza; Seifalian, Alexander; Yazdanian, Alireza
Abstract : Orodental problems have long been managed using herbal medicine. The development of nanoparticle formulations with herbal medicine has now become a breakthrough in dentistry because the synthesis of biogenic metal nanoparticles (MNPs) using plant extracts can address the drawbacks of herbal treatments. Green production of MNPs such as Ag, Au, and Fe nanoparticles enhanced by plant extracts has been proven to be beneficial in managing numerous orodental disorders, even outperforming traditional materials. Nanostructures are utilized in dental advances and diagnostics. Oral disease prevention medicines, prostheses, and tooth implantation all employ nanoparticles. Nanomaterials can also deliver oral fluid or pharmaceuticals, treating oral cancers and providing a high level of oral healthcare. These are also found in toothpaste, mouthwash, and other dental care products. However, there is a lack of understanding about the safety of nanomaterials, necessitating additional study. Many problems, including medication resistance, might be addressed using nanoparticles produced by green synthesis. This study reviews the green synthesis of MNPs applied in dentistry in recent studies (2010–2021).